Rendu-Osler-Weber syndrome: A family investigation and review - V G Mahima; Karthikeya Patil; Madhur Kapoor; Shalini Kalia (Wolters Kluwer Medknow Publications, 2009)
Rendu-Osler-Weber syndrome is a rare genetic condition characterized by mucocutaneous and visceral fibrovascular dysplasia leading to multiple macular or papular vascular lesions of skin, mucosal surfaces and occasionally viscera that show tendency towards hemorrhage. The orofacial features of the condition in an affected family and in particular a 33-year-old Indian male patient, are illustrated along with summarization of management aspects in a dental setup.